Biofabrication of Acer palmatum-Mediated Multifunctional CuO Nanoparticles for Dye Removal, Antibacterial-Antifungal Activity, and Molecular Docking - Sazak, Cansu; Attar, Azade; Yilmaz, Alper; Yapaoz, Melda Altikatoglu (AMER CHEMICAL SOC, 2023)
Copper oxide nanoparticles (CuONPs) are used in many fields from electronics to medicine due to their multifunctionality, and therefore, their production with environmentally friendly methods is a current issue. In this study, biofabricated CuONPs were obtained by using the leaf extract of Acer palmatum plant originating from the Far East to enlighten the characteristics of the novel nanoparticles differentiating from those existing in the literature. Multifunctional nature of the CuONPs was evaluated by the antibacterial, antifungal, and decolorative applications and also by performing molecular docking analysis. The fabricated CuONPs were characterized using ultraviolet-visible spectroscopy (UV-vis), Fourier-transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), and dynamic light scattering (DLS). The absorbance seen at 270 nm in the SPR band obtained by UV-vis spectroscopy proved the presence of CuONPs, while the 602, 560, and 540 cm(-1) vibrations obtained in the FT-IR spectroscopy indicated the same result. SEM images proved that the nanoparticles were in spherical form with sizes ranging from 140 to 225 nm. The result of DLS analysis showed that the average particle size was 229 nm in diameter, and CuONPs had monodisperse systems (polydispersity index, 0.184). The dye removal potency of CuONPs was also investigated by using remazol brilliant blue R (RBBR) and napthol blue black (NBB). Decolorizations (74 and 86%) of RBBR and NBB were obtained in 90 min at 50 degrees C, respectively. The strong antibacterial properties of the synthesized CuONPs were observed on both Gram (-) and Gram (+) bacterial strains by disk diffusion and optical analyses, and their antifungal activity was close to that of Amphotericin B, which was applied as a positive control. Molecular docking analysis was performed with Escherichia coli dihydrofolate reductase and Staphylococcus aureus DNA Gyrase B to analyze the antibacterial mechanisms of CuONP and observed that they exhibit good interactions with their targets with binding energies of -12.562 and -8.797 kcal/mol, respectively. Our findings suggested that CuONPs are crucial in the mechanisms of folate metabolism and DNA replication associated with bacterial proliferation. This work will provide significant guidance for the biofabrication of CuONPs and their medical and industrial applications.
Keywords: OXIDE NANOPARTICLES; GREEN SYNTHESIS; EXTRACT; METAL; Chemistry